2006
DOI: 10.1021/jm0601755
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic Pyrylium Salts in the Synthesis of Efficient Pyridinium-Based Cationic Lipids, Gemini Surfactants, and Lipophilic Oligomers for Gene Delivery

Abstract: Several new classes of pyridinium cationic lipids were synthesized and tested as gene delivery agents. They were obtained through a procedure that generates simultaneously the heterocyclic ring and the positively charged nitrogen atom, using lipophilic pyrylium salts as key intermediates that react with primary amines, yielding pyridinium salts. The choice of the appropriately substituted primary amine, diamine or polyamine, allows the design of the shape of the final lipids, gemini surfactants, or lipophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
148
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(154 citation statements)
references
References 64 publications
6
148
0
Order By: Relevance
“…The potential use of surfactants in pharmaceutical and biological applications 1,2,3,4,5,6 makes the evaluation of cytotoxicity and environmental behaviour of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…The potential use of surfactants in pharmaceutical and biological applications 1,2,3,4,5,6 makes the evaluation of cytotoxicity and environmental behaviour of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…Tosylate (4) was condensed with 4-amino-1-butanol in N,N-dimethylformamide (DMF) at 90°C to yield 5. Protection of the amino nitrogen in 5 with a Ntert-butoxycarbonyl (Boc) group, esterifcation of the resulting alcohol (6) as the tosylate, and condensation of the tosylate (7) and 4-amino-1-butanol gave the corresponding primary alcohol (8). After protecting the amino nitrogen of 8 with N-Boc, the terminal hydroxyl group was mesylated with methanesulfonyl chloride (MsCl) to yield 10.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of 4,9-diaza-4,9-di-(tert-butoxycarbonyl)dodecane-1,12-diamine 8) with ptoluenesulfonyl chloride (TsCl) in the presence of triethylamine (TEA) in CH 2 Cl 2 gave p-toluenesulfonamide compound 18 in 49% yield, and then the terminal primary amino group in 18 was converted to guanidino compound (20) by treating 18 with N,NЈ-bis(tert-butoxycarbonyl)-S-methylisothiourea in CH 2 Cl 2 . Finally, the Boc protecting groups of 20 were removed using 36% HCl in tetrahydrofuran (THF) to give the desired compound TsSPMG (2a).…”
Section: Resultsmentioning
confidence: 99%
“…The liposomes containing lipid 2d were the least active. It was found that heterocyclic cationic lipids containing imidazolinium (Solodin et al, 1995) or pyridinium polar heads (Ilies et al, 2006) reveal a higher TE and a reduced level of cytotoxicity in comparison with the classical transfectants. To study the influence of this type of heterocyclic polar head on the TE, the cholesterol-based lipids containing heterocyclic amine connected to the cholesterol residue via urethane (4a-f, 6a), ether (5a-5h) and ester linkers (6b-f) were synthesized (Gao & Hui, 2001;Bajaj et al, 2008c;Medvedeva et al, 2009).…”
Section: Monocationic Lipidsmentioning
confidence: 99%